2015
DOI: 10.3899/jrheum.141447
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Use of Complementary and Alternative Medicine for Korean Patients with Rheumatoid Arthritis

Abstract: Our study found, within a year, an incidence rate of 10.5% for new CAM use among patients with no previous experience with CAM. Sex, depression, and household type were significantly associated with new CAM use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
(31 reference statements)
4
34
1
Order By: Relevance
“…CAM use is common in patients with chronic disease, and the frequency of its use in RA has been well described, especially in traditional Asian societies. [11][12][13]30,31 Singapore is a developed country with good healthcare facilities and outcomes; yet traditional beliefs and therapies remain deeply ingrained, with widespread practice of and belief in CAM, especially in patients with chronic musculoskeletal disease or chronic pain. CAM users were more likely to be older, Chinese and non-English speaking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAM use is common in patients with chronic disease, and the frequency of its use in RA has been well described, especially in traditional Asian societies. [11][12][13]30,31 Singapore is a developed country with good healthcare facilities and outcomes; yet traditional beliefs and therapies remain deeply ingrained, with widespread practice of and belief in CAM, especially in patients with chronic musculoskeletal disease or chronic pain. CAM users were more likely to be older, Chinese and non-English speaking.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Several studies have examined the prevalence and predictors of CAM use; however, its impact has not been previously studied. [11][12][13][14] Owing to the high prevalence of CAM use previously reported in Singapore, 14 and from our clinical observation of many patients trying CAM prior to consulting their primary care physician (PCP), we hypothesized that the use of CAM may impact on early rheumatologist assessment and initiation of DMARD therapy.…”
mentioning
confidence: 99%
“…All HILI cases in our study were classified as mixed type. However, recent studies have shown that all HILI cases were of hepatocellular type (Han et al, ; Kim et al, ; Woo et al, ). Similarly, in a systematic review, 97 HILI cases consisted of 74.7% hepatocellular type, 10.8% cholestatic type, and 14.5% mixed type (Lee, Kim, Lee, & Son, ).…”
Section: Discussionmentioning
confidence: 99%
“…All HILI cases in our study were classified as mixed type. However, recent studies have shown that all HILI cases were of hepatocellular type (Han et al, 2015;Kim et al, 2011;Woo et al, 2015).…”
Section: Incidence Risk Of Lea In Each Rdmentioning
confidence: 99%
See 1 more Smart Citation